2019
DOI: 10.1111/asj.13170
|View full text |Cite
|
Sign up to set email alerts
|

The response of gene expression associated with intramuscular fat deposition in the longissimus dorsi muscle of Simmental × Yellow breed cattle to different energy levels of diets

Abstract: This study was designed to estimate dietary energy level on intramuscular fat (IMF) deposition in Simmental × Yellow breed cattle. Results showed that ultimate weight and average daily gain in high and medium energy groups were significantly higher than low‐energy group, yet feed conversion ratio was significantly lower. IMF content was significantly increased by dietary energy increasing, whereas longissimus muscle shear force significantly decreased. Serum‐free fatty acids, triglycerides and glucose signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
5
1
Order By: Relevance
“…Intramuscular fat deposition is influenced by numerous factors, such as breed, genotype, age, and nutrition (Jeong et al, 2013 ). Luccia et al ( 2013 ) and Zhang and Guan ( 2019 ) found that improving dietary energy levels would increase the intramuscular fat content and decrease shear force, thus improving meat quality. A significant increase in crude fat content was observed in T50, whereas no differential shear force was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular fat deposition is influenced by numerous factors, such as breed, genotype, age, and nutrition (Jeong et al, 2013 ). Luccia et al ( 2013 ) and Zhang and Guan ( 2019 ) found that improving dietary energy levels would increase the intramuscular fat content and decrease shear force, thus improving meat quality. A significant increase in crude fat content was observed in T50, whereas no differential shear force was detected.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation period was 7 days, and the experimental period lasted for 60 days. The experimental period was determined based on the timing of short-term fattening in beef cattle [ 1 , 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several nutritional factors can affect beef cattle production, such as the roughage vs. concentrate ratio, glucose/starch availability, dietary energy and protein levels, and stage-specific feeding systems [ 1 , 2 ]. A growth stage-specific feeding system has generally been applied to produce highly marbled beef.…”
Section: Introductionmentioning
confidence: 99%
“…The IMF of longissimus dorsi and biceps femoris muscle, and carcass lean content in Jinhua and Landrace pigs were shown in Fig 1 Pervious results have shown that many factors affected IMF and carcass lean content, such as genotypes, nutrition, age and so on (Insausti et al, 2005;Zhang and Guan, 2019). Carcass lean and IMF content is essential for eating quality, palatability, taste and flavor of meat (Huang et al, 2012).…”
Section: Carcass Lean and Imf Contentmentioning
confidence: 99%